Gastrointestinal Amyloidosis: An Unusual Case Where Protein-Losing Enteropathy is Associated to Malabsorption - Tirotta Daniela; Durante Vittori (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Introduction: The systemic amyloidosis usually doesn't save the digestive tract, but this involvement is present in approximately 60% of patients with AA Amyloidosis and only in 8% and 1% of patients with AL Amyloidosis (respectively through biopsy and clinically). Beside gastrointestinal involvement is rarely symptomatic and clinical events are not specific. Enteropathy protein-losing is a rare condition caused by excessive loss of serum protein in the gastrointestinal tract, resulting in hypoproteinaemia, edema, and, sometimes, pleural/pericardial effusions. The diagnosis should be taken into account only when other causes have been excluded. Gastrointestinal AL amyloidosis usually appears with constipation and mechanical obstruction/ pseudobstruction, on the contrary enteropathy protein-losing and malabsorption are rare. Case report: We report the case of a 59-year -old patient, with AL amyloidosis, who suffered from weight loss and ascites effusion related to an AL amyloidosis.   Discussion: The case is unusual, both because of the extension in the gastrointestinal tract  and for its unusual clinical presentation as enteropathy protein-losing associated with malabsorption.